Effect of Dietary Palm Kernel Meal Supplementation on Growth Performance, Blood Metabolites, Microbial Population and Carcass Characteristics of Growing-Meat Quails - Boontiam , Waewaree; Kittipongpysan, Sumetee (International Journal of Poultry Science, 2019)
Objectives: This study aimed to investigate the effects of palm kernel meal (PKM) supplementation on the growth performance, blood metabolites, gut microbiota and carcass characteristics of growing-meat quails. Materials and Methods: A total of 480 male growing-meat quails (21-42 days old) were randomly assigned to 4 treatment groups of 120 quails each. Four treatments were randomly assigned to five replicates each in a completely randomized design. The four treatments were basal diet without PKM supplementation (CON), basal diet with 4% PKM (PKM4), basal diet with 8% PKM (PKM8) and basal diet with 12% PKM (PKM12). Results: The final body weight and body weight gain were higher in the PKM4 group than the PKM12 group (p≤0.05). The PKM4 and PKM8 groups showed a linear relationship between the amount of PKM and body weight (p = 0.014 and p = 0.016, respectively). The uric acid concentration was significantly lower in the PKM4 than in the other treatment groups (p≤0.05). The relative weight of eviscerated carcasses increased in the PKM8 group (p≤0.05). The PKM8 group also had a higher thymus weight than the CON group (p≤0.05). Moreover, PKM supplementation significantly decreased the number of Salmonella enteritidis and Escherichia coli and significantly increased the number of Lactobacillus spp. Conclusion: Growing-meat quails that received a diet supplemented with 8% PKM showed improvements in growth performance, protein utilization, relative carcass and thymus weights and gut microflora, with no hepatic damage.